STUDY OF VOLATILE COMPONENTS OF THE PLANT PHLOMOIDES CANESCENS (Scientific journal of the Fergana State University, 2023)
The article presents the results of the quantitative determination of the components of the essential oil fraction in the organs of the medicinal plant Phlomoides canescens, belonging to the family of labiaceae. Samples of leaves and flowers of the plant were collected in the highlands of the Fergana region. The experiment was carried out by GC-MS on an Ajilent 7890 GC-MS instrument. A total of 54 substances were identified in two plant organs. Issues related to the amount of substances and the appearance of artifacts depending on the experimental conditions are discussed.